Cortical Activation Patterns Correlate with Speech Understanding After Cochlear Implantation. Issue 3 (May 2016) - Olds, Cristen; Pollonini, Luca; Abaya, Homer; Larky, Jannine; Loy, Megan; Bortfeld, Heather; Beauchamp, Michael S.; Oghalai, John S.
Abstract : Objectives: Cochlear implants are a standard therapy for deafness, yet the ability of implanted patients to understand speech varies widely. To better understand this variability in outcomes, the authors used functional near-infrared spectroscopy to image activity within regions of the auditory cortex and compare the results to behavioral measures of speech perception. Design: The authors studied 32 deaf adults hearing through cochlear implants and 35 normal-hearing controls. The authors used functional near-infrared spectroscopy to measure responses within the lateral temporal lobe and the superior temporal gyrus to speech stimuli of varying intelligibility. The speech stimuli included normal speech, channelized speech (vocoded into 20 frequency bands), and scrambled speech (the 20 frequency bands were shuffled in random order). The authors also used environmental sounds as a control stimulus. Behavioral measures consisted of the speech reception threshold, consonant-nucleus-consonant words, and AzBio sentence tests measured in quiet. Results: Both control and implanted participants with good speech perception exhibited greater cortical activations to natural speech than to unintelligible speech. In contrast, implanted participants with poor speech perception had large, indistinguishable cortical activations to all stimuli. The ratio of cortical activation to normal speech to that of scrambled speech directly correlated with the consonant-nucleus-consonant words and AzBio sentences scores. This pattern of cortical activation was not correlated with auditory threshold, age, side of implantation, or time after implantation. Turning off the implant reduced the cortical activations in all implanted participants. Conclusions: Together, these data indicate that the responses the authors measured within the lateral temporal lobe and the superior temporal gyrus correlate with behavioral measures of speech perception, demonstrating a neural basis for the variability in speech understanding outcomes after cochlear implantation. Abstract : Functional neuroimaging in deaf participants hearing through a cochlear implant demonstrates that activation patterns within the lateral temporal lobe and superior temporal gyrus correlate with behavioral measures of speech perception. This demonstrates a neural basis for the variability between patients in understanding speech after cochlear implantation.Supplemental Digital Content is available in the text.